2022
DOI: 10.3390/biomedicines10020387
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Load Correlates with Multiple Sclerosis-Associated Retrovirus Envelope Expression

Abstract: pHERV-W ENV and syncytin-1, the envelope proteins of the human endogenous retrovirus W family (HERV-W), have been proposed as etiological factors for MS development. In addition, herpesviruses, such as the Epstein-Barr virus (EBV) and the human herpesvirus 6A/B (HHV-6A/B), have been also strongly associated with the disease. This work aims to study the possible link between viral loads and antibody titers against EBV and HHV-6A/B and the pHERV-W ENV/syncytin-1 protein/gene expression. For this purpose, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, environmental viruses associated with MS can activate the promoters of the transactivation p HERV‐W, leading to epigenetic dysregulation that may influence the development of the disease [32]. Pérez‐Pérez et al [33] reported a positive correlation between the 12‐month variation of EBV load and the 12‐month variation of p HERV‐W ENV gene expression in RRMS patients, supporting the idea of potential transactivation of p HERV‐W by MS‐associated viruses [33]. Positive correlations were also observed between the levels of p HERV‐W protein expression and anti‐HHV‐6A/B IgM antibodies in T lymphocytes and NK cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, environmental viruses associated with MS can activate the promoters of the transactivation p HERV‐W, leading to epigenetic dysregulation that may influence the development of the disease [32]. Pérez‐Pérez et al [33] reported a positive correlation between the 12‐month variation of EBV load and the 12‐month variation of p HERV‐W ENV gene expression in RRMS patients, supporting the idea of potential transactivation of p HERV‐W by MS‐associated viruses [33]. Positive correlations were also observed between the levels of p HERV‐W protein expression and anti‐HHV‐6A/B IgM antibodies in T lymphocytes and NK cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified increased levels of HERV-W env protein within brain tissue and PBMCs from MS patients compared to healthy controls [ 149 – 152 ]. The reactivation of HERV-W and the association with MS have been proposed to be caused by an exogenous viral infection from Epstein-Barr virus [ 148 , 153 , 154 ].…”
Section: Endogenous Retroviruses Are Associated With the Progression ...mentioning
confidence: 99%
“…EBV replication in B cells triggers HERV-W and HERV-K expression [13][14][15][16] initiating a cascade of stimulation of inflammation [17][18][19] and cross reactivity with myelin oligodendrocyte protein (MOG) 20 . HERV-W and EBV expression levels are also associated and EBV and HERV-W loads are correlated in MS patients undergoing therapy 21 . An additional line of evidence linking HERV-W proteins to MS pathogenesis has shown HERV-W expression in microglia (brain-resident myeloid cells) associates with axons inducing a degenerative phenotype resulting in damage to myelinated axons 22 .…”
Section: Introductionmentioning
confidence: 99%